2008
DOI: 10.1093/molehr/gan066
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and its application for non-invasive embryo assessment in IVF

Abstract: Morphology and cleavage rate remain the mainstay of embryo assessment. However, a number of additional technologies for this application are under investigation. These include the measurement of glucose, lactate, pyruvate or amino acid levels in the embryo culture media, assessment of oxygen consumption by the embryo, genomic and proteomic profiling, and most recently, analytical examination of the embryonic metabolome. As the number of assisted reproduction cycles increases worldwide, improvements in the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
157
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 53 publications
0
157
0
5
Order By: Relevance
“…It is noteworthy that our initial studies on the application of metabolomic profiling to embryo assessment used both Raman and NIR-spectroscopies [21,22], both vibrational spectroscopies (see [16] for comparison) that can be performed on-site using small size instruments compatible with the environment of an IVF laboratory. In our more recent studies [23,24], and in the current study, we utilized NIR spectroscopy as this technology has a sensitivity and specificity comparable to Raman, and is less costly, therefore has more potential for clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that our initial studies on the application of metabolomic profiling to embryo assessment used both Raman and NIR-spectroscopies [21,22], both vibrational spectroscopies (see [16] for comparison) that can be performed on-site using small size instruments compatible with the environment of an IVF laboratory. In our more recent studies [23,24], and in the current study, we utilized NIR spectroscopy as this technology has a sensitivity and specificity comparable to Raman, and is less costly, therefore has more potential for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…As extensive data from animal models and human IVF [14][15][16] suggest that there are metabolic differences between cleavage stage embryos and blastocysts, a novel spectral model for day 5 embryos was developed as described in our previous publications [21,23,25]. Discrimination between FCA+ and FCA− embryos consisted of determining a parsimonious combination of spectral regions from the NIR metabolomic profiles that estimated pregnancy outcomes by inverse least-squares regression and genetic algorithm (GA) optimization.…”
Section: Spectral Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these results together illustrated that the embryonic beta-hCG secretion was consistent with morphological grading in blastocyst stage, and the detection of beta-hCG in culture media by ECLIA may become one of the biomarkers of embryonic development as well. The metabolomic profile was different between embryos resulted in pregnancy and embryos that did not [1,11]. Sivakumar R reported that the concentration of beta-hCG on day2 embryos did not rely on embryo development when they were transferred at blastocyst stage [4].…”
Section: Discussionmentioning
confidence: 99%